CODE-SWITCHING BETWEEN THE TEACHERS AND THE STUDENTS OF THE CONVERSATION - Siti Maryam Hamid (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2016)
This research aimed to describe code switching who used by the Teachers and the students especially kinds and functions to contribute to the interaction in conversation in the classroom. Codeswitching is an alternate use of two or more languages in the same utterance or conversation in a bilingual or multilingual conversation. Previous research has established that code-switching can be interpreted as a resource for bilingual or multilingual children to accomplish specific communicative goals. However, code-switching in educational settings has not been welcomed. Previous research has reported that code-switching in an educational context is considered as a deficit of interactional skills. To describe the functions, the researcher used a descriptive research which was conducted observation and interview. The location of this research was taken from the eighth-grade students of SMAN 1 Tombolo Pao, Gowa Regency with a number of the subject were 2 teachers and 36 students. The research findings of the study showed that teachers do code-switch in the conversation in the classroom, despite their claim that they do not. The English teachers used English and Indonesian. The English teachers made code switching for (1) to make questions, (2) unpleasant feeling, (3) to strengthen request or command, (4) repetition used for clarification reiteration of a message, (5) to give advice, (6) to create humor. And the students' used code switching to made they are easy to speak English and easy to understand what they want to say. Switching from English to Indonesian or other languages can also be employed as the communication strategy in English conversation classroom. The English teachers employ code switching to minimize either student's miscomprehension on the lesson or students’ difficulties in understanding the English lesson given by the English teachers in the classroom.Keywords: Code Switching, Teacher and Students Conversation